Decrees Alhakm by-Amr Allah and his relationship with the people of Dhimah(386-411 AH/996-1020AD ) - Younis, Mohsen; Jame, Ramia (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The ruling Fatimid Caliph, Alhakm by-Amr Allah, is one of the most closed political figures in the history of Islamic Egypt. The " Alhakm " did not do much to govern himself until he issued many extraordinary social "records" and renounced the religious tolerance of his Fatimid caliphs He issued a number of records limiting their religious freedom, but the " Alhakm " did not continue this policy towards the people of the Dhimah, But issued four years before his disappearance (411 AH/1020AD) several decrees to free the freedom of worship for Christians and Jews.